Philosophers and Allegorist Philosophers in Ancient Greece - Stadler, Thiago David (Romanitas - Revista de Estudos Grecolatinos, 2026)
In this article, I propose to investigate the notion of allegory as a mediating mechanism between philosophy and mythical narratives. The Greek allegory, also known in historiography as the “allegory of the poets,” was an interpretative phenomenon aimed at preserving the explanatory value of myths and the morality expressed by poets by constructing a hidden meaning within the narrative structure. Thus, between myth and philosophy, allegory – or more precisely, allegoresis – emerges as an interpretative method that, in addition to defending poetic traditions, recontextualizes the doctrinal richness of myths. Ultimately, allegorical interpretation, or allegoresis, added complexity to a world that questioned the cognitive and educational value of poetry. Therefore, I argue that the debate between myth and philosophy, as well as between poets and philosophers, can be better understood through the inclusion of the so-called allegorist philosophers.
Keywords: Allegory; Allegoresis; Philosophy; Myth